The semantic web real-world applications from industry - Cardoso, Jorge (Semantic web and beyond, computing for human experience, 2008)
Semantic web: real-world applications from industry offers a glimpse into the opening door of semantic technologies by means of concentrated examples of semantic applications in real business environments. For quite a while, there has been evidence from academic research and early industrial prototypes that semantic technology can help humans and machines substantially in accessing and using the unprecedented, and exponentially growing, amount of information that the World Wide Web provides. Now semantic technology is moving from academic and industrial research into real products and applications. This book provides a series of case studies which demonstrate how real benefits can be derived from the adoption of semantic technology in popular business domains, such as telecommunication, B2B integration, healthcare, education, and others. Semantic Web: Real-World Applications from Industry summarizes state-of-the art expertise and practical experiences from outstanding technology showcases. This volume was written as a joint effort of leading experts in the field of semantic technology from various backgrounds and countries, including industry, academia, and government agencies. It combines a detailed description of the challenges and technical solutions with a discussion of the actual results and a wealth of lessons learned, which will be invaluable for future investments into semantic technology. Semantic web: real-world applications from industry was designed for industry professionals and researchers interested in the current state and future of semantic technology. This book is also suitable as a secondary advanced-level text or reference for students in computer science. Foreword by Michael L. Brodie, Chief Scientist, Verizon Communications, Cambridge, USA . Semantic enterprises -- The future of the semantic web for enterprises -- The enterprise semantic web -- Finance and government -- Semantic web technologies for the financial domain -- Intelligent search engine for online access to municipal services -- Healthcare and life sciences -- Ontology-based data integration for biomedical research -- Active semantic electronic medical records -- Education -- Targeting learning resources in competency-based organizations -- Developing course management systems using the semantic web -- Business and customer management -- Integration of customer information using the semantic web -- Business process management and semantic technologies -- Enterprise management and security -- Ontology-based knowledge management in the steel industry -- Bringing semantic security to semantic web services.